2019
DOI: 10.1136/bmjopen-2018-027925
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the association between peripheral inflammatory cytokines and generalised anxiety disorder

Abstract: ObjectiveInflammation has been implicated in the aetiology of mental illness. We conducted the first systematic review and meta-analysis of the association between peripheral markers of inflammation and generalised anxiety disorder (GAD).DesignSystematic review and meta-analysis of studies measuring peripheral cytokine levels in people with GAD compared with controls.Data sourcesMEDLINE (1950–), EMBASE (1947–), PsycINFO (1872–) and Web of Science (1945–) databases up until January 2018.Eligibility criteriaPrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
104
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 58 publications
6
104
1
Order By: Relevance
“…Elevated cytokines are related to decreased levels of serotonin, which may result in depression and cognitive dysfunction (Sohani and Samaan, 2012). While it appears anxiety is related to an elevated inflammatory response in healthy individuals, there is less evidence of cytokines playing a role (Costello et al, 2019). However, higher anxiety is associated with inflammatory markers in patients with diabetes (Brennan et al, 2009), and inflammation during acute coronary syndrome has been shown to predict anxiety and cognitive symptoms of depression (Steptoe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated cytokines are related to decreased levels of serotonin, which may result in depression and cognitive dysfunction (Sohani and Samaan, 2012). While it appears anxiety is related to an elevated inflammatory response in healthy individuals, there is less evidence of cytokines playing a role (Costello et al, 2019). However, higher anxiety is associated with inflammatory markers in patients with diabetes (Brennan et al, 2009), and inflammation during acute coronary syndrome has been shown to predict anxiety and cognitive symptoms of depression (Steptoe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Similar basal anti-inflammatory effect was observed before by antiepileptic drugs that inhibits neuronal sodium channels like vinpocetine, carbamazepine and lamotrigine 30,50 . This basal inhibition might be clinically relevant to the current PGB-indicated conditions where elevated basal levels of these cytokines were clinically observed [7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Discussionmentioning
confidence: 76%
“…Of note, in the current report we have focused on the effects of PGB on peripheral inflammatory responses. Although neuroinflammation per se was not investigated in this study, our results might give some clues to the effect of PGB on peripheral inflammation observed in PGB-indicated conditions (neuropathic pain conditions, fibromyalgia, epilepsy and generalized anxiety disorders) where inflammatory mechanisms and elevation of proinflammatory cytokines, such as IL-6, TNF-α, IL-1β and IL-2 have been documented [7][8][9][10][11]16,17 . Besides, compared to our study, similar model of inflammation and comparable doses of LPS were employed before to study these conditions [21][22][23][24] .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations